Falls and postural stability in older individuals: Implications for activities of daily living - Polastri, Paula Fávaro [UNESP]; Godoi, Daniela; Gramani-Say, Karina (Springer Nature, 2017)
The risk of falling is associated with aging-related motor and sensory declines. In fact, a higher incidence of falls has been observed in individuals of over 60 years who are known to have balance problems. The current knowledge regarding the mechanisms involved in the recovery of postural orientation and body equilibrium shows that the main changes occur as individuals become older and in those who are sedentary or are affected by some diseases. Extensive research and preventive efforts regarding the causes and consequences of falling have been conducted to better understand this issue. Fortunately, older individuals who practice regular physical activity present a healthy lifestyle and a lower risk and incidence of falling which may be associated with functioning of the postural control system. Recently, public health policies have been adopted by many countries in order to improve the quality of life of older individuals and reduce the high number of fallers among the elderly.
Keywords: Aging; Balance; Elderly public health; Falling; Older; Physical exercise; Postural control; Practice; Sensory information